Podatkovna moč v vojaškem izobraževanju - Ščavničar, Darko (Sodobni vojaški izzivi, 2023)
The rapid development, use and availability of technology is creating new opportunities in all areas of human life. The amount of data generated is enormous, followed by advances in the collection, processing and analysis of big data for a variety of purposes, such as various industries, science, healthcare and even education. Data science in education aims to better understand and improve learning processes through data–driven insights. Learning analytics studies how to use data mining, machine learning, natural language processing, visualisation and human– computer interaction approaches to help learners, educators and institutional leaders improve learning processes and teaching practices.
Keywords: analiza podatkov; data analysis; data power; learning; learning analytics; military education; podatkovna moč; učenje; učna analitika; vojaško izobraževanje